2018
DOI: 10.1155/2018/3965054
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and Plasma Membrane Events in Cholesterol Transport and Homeostasis

Abstract: Cholesterol transport between intracellular compartments proceeds by both energy- and non-energy-dependent processes. Energy-dependent vesicular traffic partly contributes to cholesterol flux between endoplasmic reticulum, plasma membrane, and endocytic vesicles. Membrane contact sites and lipid transfer proteins are involved in nonvesicular lipid traffic. Only “active" cholesterol molecules outside of cholesterol-rich regions and partially exposed in water phase are able to fast transfer. The dissociation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 189 publications
(193 reference statements)
1
55
0
1
Order By: Relevance
“…The resultant CEs are stored in lipid droplets in the cytosol before being secreted (Das et al, 2014). Thus, to preserve cholesterol homeostasis, the cell maintains crosstalk between the PM, where the bulk of the cell's cholesterol resides, and the ER, where the enzymatic activities that regulate cholesterol levels reside (Litvinov et al, 2018). This crosstalk is believed to be controlled by an as-yet-unknown sensor in the ER that triggers communication between the PM and the intracellular ER regulatory pool of cholesterol where ACAT1 is located (Lange et al, 1999;Infante & Radhakrishnan, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant CEs are stored in lipid droplets in the cytosol before being secreted (Das et al, 2014). Thus, to preserve cholesterol homeostasis, the cell maintains crosstalk between the PM, where the bulk of the cell's cholesterol resides, and the ER, where the enzymatic activities that regulate cholesterol levels reside (Litvinov et al, 2018). This crosstalk is believed to be controlled by an as-yet-unknown sensor in the ER that triggers communication between the PM and the intracellular ER regulatory pool of cholesterol where ACAT1 is located (Lange et al, 1999;Infante & Radhakrishnan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, when in excess, "accessible" cholesterol in the PM cholesterol pool will be proportionally transported to the ER cholesterol pool, where it will trigger feedback responses to maintain homeostasis (Das et al, 2014;Infante & Radhakrishnan, 2017;Litvinov et al, 2018). It has been suggested that this trafficking is regulated by cholesterol-sensing proteins and/or a specific cholesterol-sensing membrane domain in the ER associated with ACAT1 (Lange et al, 1999).…”
mentioning
confidence: 99%
“…We uncovered a clear separation of the samples by their location using hierarchical clustering dendrogram (Fig 3D). In BM-Ad, proteins involved in cholesterol transport (apoliproproteins APO-A2, -C1 and -C4) and hydrolysis, such NCEH1 (Neutral Cholesterol Ester Hydrolysis) and LIPA (Lipase A) (Litvinov et al, 2018), were enriched. This cholesterol-oriented metabolism in BM-Ad is strengthening by the enrichment of several proteins involved in cholesterol biosynthesis and statin pathways (Fig EV3C).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, when in excess, a pool of "active" cholesterol in the PM will be proportionally transported to the ER cholesterol pool, where it will trigger feedback responses to maintain homeostasis (7)(8)(9). It has been suggested that this trafficking is regulated by cholesterolsensing proteins and/or a specific cholesterol-sensing membrane domain in the ER associated with ACAT1 (10).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to preserve cholesterol homeostasis, the cell maintains a crosstalk between the PM, where the bulk of cholesterol resides, and the ER, where the enzymatic activities that ensure cholesterol levels reside (9). This crosstalk is believed to be controlled by an as-yet-unknown sensor in the ER that triggers the communication between the PM and the intracellular ER regulatory pool of cholesterol where ACAT1 resides, or MAM (8,10).…”
mentioning
confidence: 99%